Radiation and Drought Impact Residual Leaf Conductance in Two Oak Species With Implications for Water Use Models - Qin, Haiyan; Arteaga, Carles; Chowdhury, Faqrul Islam; Granda, Elena; Yao, Yinan; Han, Ying; Resco de Dios, Víctor (Frontiers in Plant Science, 2020)
Stomatal closure is one of the earliest responses to water stress but residual water losses may continue through the cuticle and incomplete stomatal closure. Residual conductance (gres) plays a large role in determining time to mortality but we currently do not understand how do drought and shade interact to alter gres because the underlying drivers are largely unknown. Furthermore, gres may play an important role in models of water use, but the exact form in which gres should be incorporated into modelling schemes is currently being discussed. Here we report the results of a study where two different oak species were experimentally subjected to highly contrasting levels of drought (resulting in 0, 50 and 80% losses of hydraulic conductivity) and radiation (photosynthetic photon flux density at 1,500 μmol m-2 s-1 or 35-45 μmol m-2 s-1). We observed that the effects of radiation and drought were interactive and species-specific and gres correlated positively with concentrations of leaf non-structural carbohydrates and negatively with leaf nitrogen. We observed that different forms of measuring gres, based on either nocturnal conductance under high atmospheric water demand or on the water mass loss of detached leaves, exerted only a small influence on a model of stomatal conductance and also on a coupled leaf gas exchange model. Our results indicate that, while understanding the drivers of gres and the effects of different stressors may be important to better understand mortality, small differences in gres across treatments and measurements exert only a minor impact on stomatal models in two closely related species.